Analysis of the Effect of Feed Rate, Spindle Speed and Coolant on Surface the Roughness of ST 37 Steel in the Turning Process - Rahmatul Fauzan Mulyadi; Syahril; Rifelino; Zainal Abadi (Unversitas Negeri Padang, 2026)
Surface roughness is an important parameter in turning processes, as it directly affects the performance and service life of mechanical components. This study aims to examine the influence of feed rate, spindle speed, and coolant application on the estimated surface roughness (Raest) of ST 37 steel under conventional turning conditions. A 2³ full factorial experimental design was employed, involving eight treatment combinations consisting of two feed rate levels (0.040 and 0.100 mm/rev), two spindle speed levels (315 and 400 rpm), and two cooling conditions (with and without coolant). Surface roughness estimation was carried out using digital image analysis with ImageJ software based on optical microscope images. The analysis utilized gray-level intensity distributions, which were then converted into roughness values using an empirical scaling approach. The results indicate that increasing the feed rate led to a rise in Raest ranging from 1.74% to 7.11%, while higher spindle speeds contributed to an increase in surface roughness between 4.54% and 11.91%. In contrast, the use of coolant reduced surface roughness by an average of 9.20%, mainly due to its role in minimizing heat and friction during machining. The optimal parameter combination was obtained at a spindle speed of 315 rpm and a feed rate of 0.040 mm/rev with coolant, producing an Raest value of 1.495 µm, which falls within ISO roughness class N7. Overall, all specimens were classified within ISO N7, indicating a semi-finishing surface quality.